Pemasaran Bank Syariah Berbasis Tekhnologi Revolusi Industri 4.0 - Dedeng Irawan; Sugianto Sugianto; Saparuddin Siregar (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Islamic bank marketing must be able to change the way of human life and work processes as a whole, in order to support the advancement of information technology to be able to synergize in the world of life with marketing media that can be used to market products that exist in Islamic banks, so that all these products can be recognized by all customers who are users of Islamic bank products. In this research, it is hoped that it can add scientific references in knowing the products in Islamic banking, especially those that are directly related to Economic Construction in the Technology 4.0 era. by using the SWOT Analysis technique. This paper will use qualitative research with a case study approach, namely the author tries to reveal real life so that the collected data is analyzed in detail obtained from many sources, both from interviews, direct observations or data results that have been published by previous researchers. The findings in this study are that Islamic banks can choose the right strategy to synergize with the 4.0 industrial revolution, namely by using SWOT analysis. Key Word: Sharia Bank Marketing, Industry Revolution Technology 4.0,